Cognitive Levels of Pragmalinguistic Typology and German Text Comprehension - Szabó, Erzsébet; Stranovská, Eva; Ficzere, Anikó (Journal of Education Culture and Society, 2023)
Aim. The research aim is to find out the correlation between the comprehension of read texts in German and the different cognitive linking levels such as the propositional, the epistemic and the speech of act level. Methods. In the first phase of the research, we used qualitative content analysis to identify the different cognitive levels in the texts. After that we used a didactic test to determine the text comprehension in German at the A2 language proficiency level. Results. A statistically significant positive relationship was found between reading comprehension performance in German and the propositional level. This means, higher performance in reading comprehension of German texts is manifested if the read texts contain indicators such as indicative sentences and adverbial tenses. Subsequently, we find a tendency correlation between the comprehension of German texts and the level of speech acts. No statistically significant relationship was found in the variable of epistemic level and German text comprehension. Conclusion. Our research showed that the epistemic level indicators and the speech act level indicators made it difficult for the learners to comprehend German texts, for this reason it would be necessary that after mastering the simpler phenomena such as the indicative mood, they should fluently start to deal with the indicators of the above levels. In the educational process, it is necessary to focus on the training of word types, on explaining the meanings of these words or expressions in order to develop and broaden the vocabulary of learners.